2016
DOI: 10.1159/000443447
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Vitamin C Supplementation on Kidney Function and Vascular Reactivity Following Renal Ischemic Injury in Mice

Abstract: Background/Aims: Renal ischemia/reperfusion injury (IRI) is a very common clinical event and usually leads to ischemic acute renal failure (ARF). In the present study, we investigated the protective role of vitamin C in renal function and renal arterial relaxation following ischemic injury. Methods: IRI model in mice was used. Various biochemical parameters including nitric oxide (NO), reduced glutathione (GSH), total reactive oxygen species (ROS) level and superoxide dismutase (SOD) were examined. Doppler was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 50 publications
1
24
0
Order By: Relevance
“…GSH is the main safeguard against oxidative damage by promoting the cellular system of protection against oxidative damage [32]. One related study showed that Vitamin C intake increased GSH levels after renal ischemia injury [33]. GSH, along with glutathione peroxidase, acts with hydrogen peroxide to block the peroxidation chain reaction and defend protein thiol groups from non-enzymatic oxidation [34].…”
Section: Discussionmentioning
confidence: 99%
“…GSH is the main safeguard against oxidative damage by promoting the cellular system of protection against oxidative damage [32]. One related study showed that Vitamin C intake increased GSH levels after renal ischemia injury [33]. GSH, along with glutathione peroxidase, acts with hydrogen peroxide to block the peroxidation chain reaction and defend protein thiol groups from non-enzymatic oxidation [34].…”
Section: Discussionmentioning
confidence: 99%
“…The latter study demonstrated cytoprotective and antioxidant efficacy within a short period of I/R, and with one bolus dose of vitamin C pre-ischemia, suggesting that it may be beneficial and practical in defined elective procedures, such as renal transplantation. A renal ischemic injury study in mice also showed improved kidney function and decreased tubule cell injury with vitamin C pretreatment that was associated with decreased renal lipid oxidation and improved SOD and GSH levels [ 84 ]. In this study, vitamin C also significantly improved kidney NO • levels and in vivo arterial resistance and vascular reactivity of excised renal arteries, indicating that ascorbate protects vascular function by direct ROS scavenging, and/or via up-regulation of SOD, to prevent renal injury.…”
Section: Vitamin C and Renal Protectionmentioning
confidence: 99%
“…In other respects, however, the kidney is vulnerable to damage by many disease processes given such as renal ischemia/ reperfusion (I/R) injury (RI/RI) during the perioperative period [1, 2]. Renal sensitivity to I/R injury is found to be increased in streptozotocin (STZ)-induced diabetic rats [3], and in fact, RI/RI frequently occurs in diabetic patients [4] and often emerges as one of the dangerous complications of this procedure [5, 6]. In such a condition, patients may need renal transplantation in their later life when diabetic nephropathy occurs [7].…”
Section: Introductionmentioning
confidence: 99%